Variables Related to Communication About Prognosis Between Nurses and Patients at Heart Failure Clinics in Sweden and the Netherlands. Issue 2 (March 2018) - van der Wal, Martje H.L.; Hjelmfors, Lisa; Mårtensson, Jan; Friedrichsen, Maria; Strömberg, Anna; Jaarsma, Tiny
Abstract : Background: In contrast to recommendations in recent guidelines, prognosis is not optimally discussed with patients with heart failure (HF). Reasons for not doing so can be related to both patient and provider characteristics. Purpose: The purpose of the study was to explore which patient- and nurse-related variables influence discussing prognosis with patients at an HF clinic. Method: Data from a previous survey on attitudes and clinical practice of HF nurses on discussing prognosis that was conducted in Sweden and the Netherlands were combined with data from a registration on topics that nurses discussed with their patients during a prespecified week at the HF clinic. Multivariable logistic regression analysis was performed to assess which variables are related to discussing prognosis. Results: A total of 275 HF nurses (mean age, 49 years) and data of 1633 patients with HF (mean age, 71 years) were included in the study. Prognosis was discussed with 42% of all patients during the visit at the HF clinic. Patients with whom prognosis was discussed were more often in New York Heart Association classes III to IV (odds ratio [OR], 1.81; 95% confidence interval [CI], 1.44–2.26). Nurses discussing prognosis reported more knowledge on the topic (OR, 1.71; 95% CI, 1.36–2.16) and discussed more topics with the patient (OR, 1.27; 95% CI, 1.21–1.32). Dutch HF nurses were more likely to discuss prognosis compared with their Swedish colleagues (OR, 1.83; 95% CI, 1.43–2.33). Conclusions: Discussing prognosis with patients with HF by nurses at the HF clinic is related to the characteristics of patients and HF nurses. Future interventions to improve communications about prognosis therefore should have a broad approach.